Stress reactions and fractures around the elbow in athletes - McBride, A. P.; Brais, G.; Wood, T.; Ek, E. T.; Hoy, G. (Journal of Science and Medicine in Sport, 2021)
Stress fractures of the upper limb affect athletes from a wide range of sports. Athletes involved in throwing sports are particularly susceptible along with athletes from sports involving high repetitive and compressive loads such as gymnastics. Diagnosis can be made from clinical history, examination and radiography in some cases however MRI imaging is often required for definitive diagnosis.The mainstay of management is rest and activity modification however advanced pathology often requires surgical management for successful resolution and return to play. In the elbow, the bones susceptible to excessive stress in sport are the distal humerus, the olecranon process of the ulna, the coronoid process of the ulna , the sublime tubercle and the radial head. In immature patients, medial epicondyle apophysis is the most common location. The article presents a narrative review of the literature.